1992
DOI: 10.1042/bj2820867
|View full text |Cite
|
Sign up to set email alerts
|

Haem binding to horse spleen ferritin and its effect on the rate of iron release

Abstract: Horse spleen ferritin is shown to bind haem to generate a haemoprotein, named herein haemoferritin. A total of 14-16 haem molecules are bound per 24 subunits of ferritin. The molecular mass of the non-haem-iron-free haemoferritin has been determined to be 420 + 40 kDa, indicating that haem binding does not lead to dissociation of the 24 subunits that comprise the ferritin molecule. The functional role of the bound haem has been investigated with respect to the release of iron from the non-haem iron core. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…This can be seen by considering the basic scheme of the commonly employed in vitro reductive iron release assays (Eqs. 1 , 2 ) [ 83 85 ]: …”
Section: Furnishing Other Proteins With Iron From Ferritinsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be seen by considering the basic scheme of the commonly employed in vitro reductive iron release assays (Eqs. 1 , 2 ) [ 83 85 ]: …”
Section: Furnishing Other Proteins With Iron From Ferritinsmentioning
confidence: 99%
“…5 ), it appears that electron transfer through the ferritin protein is important in reductive release of Fe 2+ ions, at least in the small molecule studies using the assays of reactions ( 1 ) and ( 2 ). This is shown by the dependence of the overall rate of formation of Fe 2+ (L) x on the redox potential of the electron donor [ 84 , 85 ].…”
Section: Furnishing Other Proteins With Iron From Ferritinsmentioning
confidence: 99%
“…Iron release has been the focus of numerous studies that used either a strong reducing agent, such as dithionite, or other reducers, such as superoxide anions 0;- (Monteiro et al, 1989), reduced flavins (Sirivech et al, 1974;Imai et al, 1980), or viologens (Jacobs et al, 1989). It is not clear whether the reducing molecule penetrates the protein shell by some of the channels or if a long-range electronic transfer occurs through the shell (Kadir et al, 1991;Kadir et al, 1992).…”
Section: Introductionmentioning
confidence: 98%
“…A major difference between ferritin and BFR is that, as isolated, BFR contains haem and ferritin does not. However, recent optical spectroscopic studies of horse spleen ferritin have shown that in vitro it binds the protoporphyrin IX haem group to generate haemoferritin (Kadir & Moore, 1990;Kadir et al, 1992). Approx.…”
mentioning
confidence: 99%
“…Horse spleen ferritin was obtained from the Sigma Chemical Co. (Poole, Dorset, U.K.) and the non-haem iron removed by dialysis against thioglycollic acid, at pH 4.25 and 4°C for 5 days followed by dialysis against 25 mM-phosphate buffer at pH 7 for 2 days. Haemoferritin was prepared from the resulting apoferritin by the procedure by Kadir et al (1992).…”
mentioning
confidence: 99%